β-hydroxy-β-methylbutyrate free acid supplementation may improve recovery and muscle adaptations after resistance training: a systematic review - Silva, Vagner R.; Belozo, Felipe L.; Micheletti, Thayana O.; Conrado, Marcelo [UNESP]; Stout, Jeffrey R.; Pimentel, Gustavo D.; Gonzalez, Adam M. (Elsevier, 2017)
β-Hydroxy-β-methylbutyrate free acid (HMB-FA) has been suggested to accelerate the regenerative capacity of skeletal muscle after high-intensity exercise and attenuate markers of skeletal muscle damage. Herein a systematic review on the use of HMB-FA supplementation as an ergogenic aid to improve measures of muscle recovery, performance, and hypertrophy after resistance training was conducted. This review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. We included randomized, double-blinded, placebo-controlled trials investigating the effects of HMB-FA supplementation in conjunction with resistance exercise in humans. The search was conducted using Medline and Google Scholar databases for the terms beta-hydroxy-beta-methylbutyrate, HMB free acid, exercise, resistance exercise, strength training, and HMB supplementation. Only research articles published from 1996 to 2016 in English language were considered for the analysis. Nine studies met the criteria for inclusion in the analyses. Most studies included resistance-trained men, and the primary intervention strategy involved administration of 3 g of HMB-FA per day. In conjunction with resistance training, HMB-FA supplementation may attenuate markers of muscle damage, augment acute immune and endocrine responses, and enhance training-induced muscle mass and strength. HMB-FA supplementation may also improve markers of aerobic fitness when combined with high-intensity interval training. Nevertheless, more studies are needed to determine the overall efficacy of HMB-FA supplementation as an ergogenic aid.
Keywords: Calcium HMB; HMB free acid; Muscle mass; Sports nutrition; Supplementation